Drill bit noise imaging without pilot trace, a near-surface interferometry example - Asgharzadeh, Mehdi; Grant, A.; Bona, Andrej; Urosevic, Milovan (COPERNICUS GESELLSCHAFT MBH, 2019)
© Author(s) 2019. Acoustic energy emitted by drill bits can be recorded by geophones on the surface and processed for an image of the subsurface using seismic interferometry methods. Pilot sensors record bit signals on the drill rig and play an important role in processing geophone traces for the image. When pilot traces are not available, traces of the nearest geophone to the rig may be used in deconvolution and cross-correlation of data, but extra signal processing efforts are required to reduce the effect of source signature on cross-correlation results. In this study, we use the seismic interferometry method to image the shallow subsurface beneath a 2-D geophone array by converting geophones to virtual sources. As there is no pilot signal available for this survey, we use the nearest geophone trace for pilot cross-correlation and pilot deconvolution. We modify the spectrum of pilot cross-correlation and deconvolution results so that the effect of source function on virtual data is minimized. We then migrate the virtual shots and compare the results of interferometric imaging with the available image from 3-D (active source) survey and assess the efficiency of our approach. We show that drill bit noise data can be used to generate a reasonably accurate image of the subsurface even in the absence of pilot recordings, but the results should be checked for the appearance of virtual multiples and depth inconsistencies that are caused by errors in the migration velocity.